Neo-additive capacities and updating - Jürgen Eichberger; Simon Grant; Jean-Philippe Lefort (University of Heidelberg, Department of Economics, 2009)
This paper shows that, for CEU preferences, the axioms consquentialism, state independence and conditional certainty equivalent consistency under updating characterise a family of capacities, called Genralised Neo-Additive Capacities (GNAC). This family contains as special cases among others neo-additive capacities as introduced by Chateauneuf, Eichberger, and Grant(2007), Hurwicz capacities, and ε-contaminations. Moreover, we will show that the convex version of a GNAC is the only capacity for which the core of the Full-Bayesian Updates of a capacity, introduced by Jaffray (1992), equals the set of Bayesian updates of the probability distributions in the core of the original capacity.
urn:nbn:de:bsz:16-opus-99800
Keywords: D81; D82; 330; Ambiguity; Updating; Choquet Expected Utility; neo-additive capacities; Conditional Certainty Equivalent Consistency; Entscheidung unter Unsicherheit; Erwartungsnutzen; Theorie